An Educationally Sound Experiment?: The Ohio School of the Air, 1928–1937. Issue 2 (1st September 2022) - Myers, Nathan R.
Abstract: This article recounts the history of the Ohio School of the Air (OSA) as a technological innovation that demonstrates the promise and limitations of technology in education. The article situates the OSA within the larger progressive educational movement, detailing the OSA's rise and reasons for its decline. This article argues that, while the OSA sought to bring education to all public school pupils in Ohio, the OSA's choice of content and contributors reflected the biases of society-wide power structures related to gender, race and class that were present in US society in the early twentieth century. Though OSA founder Benjamin Darrow had a vision of a robust, radio-based curriculum that would bring culture to the masses, the OSA was ultimately derailed by financial difficulties and failed to fundamentally alter the nature of schooling.